Annual World Bank Conference on Development Economics—Global 2011 : Development Challenges in a Postcrisis World - Sepúlveda, Claudia; Harrison, Ann; Lin, Justin Yifu (Washington, DC: World Bank, 2013)
This volume presents papers from a global gathering of the world’s leading development scholars and practitioners held May 31 - June 2, 2010. Paper themes include: Environmental Commons and the Green Economy, Post-crisis Development Strategy, the Political Economy of Fragile States, Measuring Welfare, and Social Programs and Transfers.